2020
DOI: 10.11005/jbm.2020.27.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals for Bone Turnover Markers in Korean Healthy Women

Abstract: Background: Adequate suppression of bone turnover rate is important to decrease fracture risk without mineralization defect due to oversuppression. This study was performed to determine reference intervals (RIs) for 2 bone turnover markers, serum C-terminal telopeptide of type I collagen (CTX) and osteocalcin, in Korean women. Methods: A total of 461 Korean women (287 premenopausal and 174 postmenopausal) without any disease or drug history affecting bone metabolism was included. Serum CTX and osteocalcin were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
1
6
0
6
Order By: Relevance
“…The dose-response-related negative correlation of osteocalcin and handgrip strength in women was in line with previous research conducted by Moriwaki et al [34] Cho et al [35], and Smith et al [21] whose findings showed that the osteocalcin level was higher in women than in men, that it was especially higher in postmenopausal women, and that it was associated with impaired physical performance as osteocalcin levels increased. However, the potential confounders BMI, SMI, and DPP4i use were not adjusted for in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…The dose-response-related negative correlation of osteocalcin and handgrip strength in women was in line with previous research conducted by Moriwaki et al [34] Cho et al [35], and Smith et al [21] whose findings showed that the osteocalcin level was higher in women than in men, that it was especially higher in postmenopausal women, and that it was associated with impaired physical performance as osteocalcin levels increased. However, the potential confounders BMI, SMI, and DPP4i use were not adjusted for in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Few reference-interval studies on BTMs have been conducted with Asian populations. A Korean study of 287 premenopausal women reported a reference interval for serum CTX (Roche assay) of 101–632 ng/L with a median of 251 ng/L [ 17 ]. Serum PINP concentrations were not measured.…”
Section: Btms During the Life Course In Health And Diseasementioning
confidence: 99%
“…The above consensus statement was based on published studies and suggested universal reference intervals for plasma CTX and PINP concentrations in premenopausal women ( Table 4 ) [ 17 - 20 ]. In contrast, the Korean Society for Bone and Mineral Research consensus statement on the use of BTMs for monitoring osteoporosis treatment provided premenopausal reference intervals for PINP (19–83 µg/L, median: 40 g/L) and CTX (36–899 ng/L, median: 279 ng/L) [ 24 ].…”
Section: Btms During the Life Course In Health And Diseasementioning
confidence: 99%
“…[ 5 ] However, many factors such as individual disease, medication history, and testing protocols are involved in the application of reference values in healthy individuals without osteoporosis to patients with osteoporosis. [ 4 ] Therefore, there are no standards for the monitoring of patients and prediction of fractures using bone markers in clinical practice.…”
Section: Introductionmentioning
confidence: 99%